The Effect of Curcumin on an Animal Intestinal Ischemia/Reperfusion Model for Bacterial Translocation and Inflammatory Response - Sozen, Selim; Aziret, Mehmet; Bali, Ilhan; Emir, Seyfi; Ulgen, Yigit; Binnetoglu, Kenan; Cetinkunar, Suleyman (Int College of Surgeons, 2015)
Ischemia/reperfusion (IR) injury of the intestine is a major problem in abdominal pathological condition and is associated with a high morbidity and mortality. The purpose of the study is to investigate the effects of curcumin on the bacterial translocation incidence and inflammatory response in rats submitted to bowel ischemia reperfusion injury. Thirty-two Wistar albino rats with a weight of 200 to 250 g were used in the study. They were randomly divided into 3 groups (n = 10 for each group): sham only operated group(group I); IR group (group II); and IR + curcumin treatment group (group III). Curcumin (curcumin from Curcuma longa) 20 mg/kg/day was given orally to the curcumin group. All animals were given 109 E. Coli by orogastric intubation 12 hours before sampling. Seventy-two hours after the first operation, mesenteric lymph node and blood samples were obtained and cultured. Blood samples of 2 mL were obtained for a polymerase chain reaction study. A piece of terminal ileum was also sampled for histopathologic examination. Mesenteric lymph node and blood cultures of all control animals were positive for microbiological growth, and polymerase chain reaction results were positive in seven of the eight rats. Histopathologically, edema, vasodilatation and inflammatory cell infiltration were found to be less in the other groups in comparison to the control group. Curcumin reduced bacterial translocation in blood, hepatocellular damage, and plasma cytokine levels. Curcumin reduced the incidence of bacterial translocation in intestinal I/R. rats. These results suggest that Curcumin would be clinically useful in the treatment of intestinal I/R injury.
Keywords: Bacterial translocation; Curcumin; Ischemia/reperfusion injury; Intestine